Implementation of Adiwiyata “Green School” in Chieving Education for Sustainable Development (Case Study at Forestry Vocational School of Pekanbaru) - Lambok P. Sagala (Kaunia: Integration and Interconnection Islam and Science, 2019)
Ministry of the Environment Indonesia launched Adiwiyata “Green School” program in 2006 for encouraging and forming environmentally friendly and cultured schools that are able to participate and carry out environmental preservation and sustainable development efforts. This paper describes Forestry Vocational School activities in achieving Adiwiyata. The paper also provides information regarding its effectiveness, and challenges during its implementation. The school has adopted Adiwiyata “Green School” since 2013. There are 4 (four) components which are used as a guideline for undertaking adiwiyata school program, including school policies, curriculum, participatory-based activities, and facilities/infrastructure that support environmental education. Adiwiyata is an effective tool in raising environmental awareness that could eventually lead to eco-behavior. However, its implementation should also be supported by other stakeholders/programs as environmental awareness and behavior do not depend solely on Adiwiyata program.